BANK LENDING TO SMALL AND MEDIUM-SIZED ENTERPRISES: THE EXPERIENCE OF UKRAINE AND POLAND - Vovk Viktoriia Yakivna; Zhezherun Yuliіa Volodymyrivna; Kostohryz Viktoriia Hryhorivna (Scientific Journal of Pedagogy and Economics, 2019)
In the conditions of implementation of the European integration strategy of Ukraine, the issues of forming competitive environment, creating additional jobs and reducing unemployment, increasing social and economic protection of the population are of particular importance. That is why the promotion of small and mediumsized enterprises remains one of the priority directions of national and regional economic policy. SMEs are a form of organization of activities that takes into account the interests of an individual, and forms conditions for improving his (her) own well-being. The main criteria for assigning an enterprise to small and medium-sized businesses are the number of employees for the reporting period and annual income. In addition, other (additional) criteria, such as the balance sheet amount in Poland, may be used. The comparative analysis of the criteria for assigning enterprises to small and medium-sized businesses indicates that the current Ukrainian legislation complies with the legal norms and requirements of the legislation of European countries. The main sources of SME financing include the own funds of business entities, loans from banking and non-banking institutions, as well as budget funds and resources from international funds, organizations, etc. Summarizing and systematizing the experience of lending to small and medium-sized enterprises in Ukraine and Poland shows that the following problems can be attributed to the main ones that restrain banks: a high level of riskiness of SMEs (especially projects "from ground zero"), a low level of transparency of economic activity of SMEs; lack of reliable collateral; low level of state support. The main problems of SME-borrowers are the high cost of credit resources; complicated loan procedures; high requirements of banks for providing loans, etc. That is why creating a supportive business environment for SMEs requires effective partnerships between government, community and business, in particular, development and implementation of state support programs for SMEs, stimulating SMEs lending, attracting external investors, and using international SMEs support experience. Complex implementation of these measures will promote socio-economic development and increase the standard of living of the population. The purpose of the article is to study the experience of lending to SMEs in Ukraine and Poland and to determine the possibilities of using foreign experience in the development of state and regional programs for support of small and medium-sized enterprises in Ukraine.